1999
DOI: 10.1097/00001756-199904060-00029
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Rheb mRNA following middle cerebral artery occlusion in the rat

Abstract: Rheb is a recently identified member of the Ras super-family and is an immediate early gene that is rapidly and transiently induced in the hippocampal granule cells by NMDA-dependent synaptic activity in the long term potentiation paradigm. The close homologies with Ras and its rapid inducibility strongly suggest that Rheb shares many biochemical and signaling properties with Ras. The present study investigated the effect of middle cerebral artery (MCA) occlusion on the expression of Rheb mRNA in the rat brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Erythropoietin has been demonstrated to defend microglia from OGD by promoting the mTOR activity and inhibiting the release of mitochondrial cytochrome C because mTOR inhibition through rapamycin silences the cellprotective function of erythropoietin [31]. Rapamycin can also enlarge the brain infarct size and increase the neurological de cit score in rats with focal cerebral ischemia, indicating that promoting mTOR activation may lead to lighter ischemic brain injury and better behavior recovery.Rhebis a necessary protein in phosphorylating of mTOR for activation.Previous study found that Rheb mRNA levels were down-regulated in parietal cortex and Lateral striatum in MCAO rats after 24h, which wasconsistent with the results of the present study [32].Our study found that Rheb expression was decreased and miR155 expression was increased on 24 h after reperfusion in MCAO/R rats. Recent study has demonstrated thatmiR-155 might regulate the expression of Rheb at the post-transcriptional levels by directly act on Rheb mRNA in vitro [25].These results suggest that miR155 may inhibit mTOR signaling pathwayby targeting Rheb in IS.…”
Section: Discussionsupporting
confidence: 93%
“…Erythropoietin has been demonstrated to defend microglia from OGD by promoting the mTOR activity and inhibiting the release of mitochondrial cytochrome C because mTOR inhibition through rapamycin silences the cellprotective function of erythropoietin [31]. Rapamycin can also enlarge the brain infarct size and increase the neurological de cit score in rats with focal cerebral ischemia, indicating that promoting mTOR activation may lead to lighter ischemic brain injury and better behavior recovery.Rhebis a necessary protein in phosphorylating of mTOR for activation.Previous study found that Rheb mRNA levels were down-regulated in parietal cortex and Lateral striatum in MCAO rats after 24h, which wasconsistent with the results of the present study [32].Our study found that Rheb expression was decreased and miR155 expression was increased on 24 h after reperfusion in MCAO/R rats. Recent study has demonstrated thatmiR-155 might regulate the expression of Rheb at the post-transcriptional levels by directly act on Rheb mRNA in vitro [25].These results suggest that miR155 may inhibit mTOR signaling pathwayby targeting Rheb in IS.…”
Section: Discussionsupporting
confidence: 93%
“…R as- h omology e nriched in b rain was identified as a gene whose expression was induced in rat brain by synaptic activity and growth factor stimulation [100, 101]. Rheb is a small GTPase that is structurally more close to Ras than to other small GTPases.…”
Section: Rhebmentioning
confidence: 99%
“…These genes include junB (Comelli et al, 1993;Hsu et al, 1993;Kamii et al, 1994a;, Zacl and PACAP (Gillardon et al, 1998), NGFIA,B,C (Lin et al, 1996;Honkaniemi et al, 1997), egr (Honkaniemi et al, 1997), Rheb (Kinouchi et al, 1999a), Arc (Kunizuka et al, 1999) and probably other lEGs. Hsp27, COX2, and PKC are induced by spreading depression (Plumier et al, 1997c;Miettinen et al, 1997;Koponen et al, 1999).…”
Section: Hemispheric Spreading Depressionmentioning
confidence: 99%